Associations of Atopic Dermatitis in Late Adolescence with Occupation, Mental Health, Income from Work and Marital Status: A National Longitudinal Study - Grigorios Theodosiou; Therese Sterner; Ayako Hiyoshi; Michael Carlberg; Åke Svensson; Scott Montgomery; Laura von Kobyletzki (Acta Dermato-Venereologica)
The main aim of this study was to evaluate longitudinal associations between atopic dermatitis (AD) in late adolescence and occupational socioeconomic group, labour market participation, income from work, and marital status later in adult life. Using Swedish population-based registry data a total of 205,394 men were included, born between 1952 and 1956 in Sweden and who underwent military conscription examination including assessment of atopic dermatitis (AD) and AD severity. The associations between AD and AD severity in late adolescence and labour market participation, income from work, marital status, and medication for anxiety and depression later in adult life were examined. In this study, men with AD in adolescence, especially those with severe AD, more often had a prescription for antidepressants or anxiolytics at the age of 50–57 years (unadjusted HR 1.55, 95% CI 1.32–1.81). Interestingly, despite increased risk of poorer mental health, AD was not found to be associated with a disadvantage in terms of occupational socioeconomic group, income from work, and unemployment benefits. Individuals with mild AD showed a lower risk of holding routine and lower technical jobs compared with men without AD. Persons with AD in late adolescence seem not to differ regarding registered partnerships and marital status compared with those without AD.